Labour market developments and their significance for VET in Germany : an overview - Ebner, Christian [Verfasser] (My University, 2015)
"The German labour market has seen substantial structural changes, especially over the past decades: there has been a major shift in labour market policy, the service industry is booming and skills requirements have changed dramatically. This article discusses these trends, offering an empirical analysis of the extent to which the German dual VET system is prepared to meet them. For this purpose, the article explores representative data for Germany and looks at the labour market integration of dual VET graduates. The basic assumption is that a mismatch between the dual VET system and the labour market will also become evident at the micro level of individuals. The results show that dual VET graduates enjoy far better protection against unemployment than people without a vocational training qualification. Likewise, they are far less likely to work in temporary employment. The dual VET system thus functions as a 'safety net'. At the same time, however, the earnings of dual VET graduates are markedly lower than those of higher education graduates. The article concludes by discussing some of the future challenges and opportunities facing the dual VET system." (Authors' abstract, BIBB-Doku)
Version of Record - Nov 23, 2015. - OnlineFirst Version of Record - Oct 26, 2015.
Keywords: G 1.2 Arbeitsmarkt; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Arbeitsmarkt; Berufliche Integration; Berufseinmündung; Zweite Schwelle; Ausbildungsabsolvent; Hochschulabsolvent; Jugendlicher ohne Berufsabschluss; Bildungschancengleichheit; Arbeitsmarktrisiko; Einkommenshöhe